The Evolution of Cholesterol-Lowering Drugs: What’s New? - Al-Masoud, Bander Mohammad Ali; Aldawood, Fawaz Saleh Saad; Alanazi, Naif Khaluf; ALHANOS, ABDULLAH Mohammed Salih; Alosaimi, Mohammed Shudayyid Motlaq; Alkhudair, Meitham Essa (Journal of Posthumanism, 2024)
The clinical utility of new medicinal products is principally established on the basis of well-conducted, randomized, controlled studies demonstrating that those products are safe and effective and provide a benefit in clinical outcome (García-Fernández-Bravo et al., 2022). For cholesterol management, low-density lipoprotein cholesterol (LDL-C) reduction represents a key modifiable risk factor for cardiovascular disease (Bardolia et al., 2021).Statins are the cornerstone of treatment, but muscle symptoms and new-onset diabetes are relatively common reasons for discontinuation. Since the landmark trials of the Icelandic physician, Akira Endo, in the mid-twentieth century, several other classes of cholesterol-lowering medications with different mechanisms of action have been developed. Understanding the pharmacokinetics, indications, and adverse effects of these agents can assist clinicians in creating individualized treatment plans (Leo Burger et al., 2022).